EFFECT OF VENTURE CAPITAL FINANCING ON THE FINANCIAL PERFORMANCE OF SMEs IN CROSS RIVER STATE - EGU USANG INAH; OLOFU MATHIAS AJOR; MANNAH ELIZABETH JACOB; UWALAKA BENEDICTA CHISOBEM; IBAYE THERESA MBONG (International Studies Journal)
This study examined the effect of venture capital financing on the financial performance of small and medium scale enterprises (SMEs) in Cross River state, Nigeria. Specifically, the study sought to determine the effect of venture capital financing on the Net sales, net profit and Return On Assets of SMEs in cross river state. The study anchored significantly on pecking order theory. Descriptive survey research design was used for the study. The population of study comprised all the SMEs in Cross River State that registered with Corporate Affairs Commission and have used venture capital. The sampling technique adopted was a two-staged sampling technique which are purposive and simple random sampling technique. Primary data were collected from respondents through structured questionnaires. Data collected were analysed using descriptive statistics of mean and standard deviation. Correlation test and analysis of variance (ANOVA) were also used. The findings therefore revealed that there was significant difference in net sales, net profit and return on assets after using venture capital financing. Hence, it was concluded that venture capital financing has significant effect on the financial performance of SMEs. Based on the finding and conclusion, it was recommended among others that fund managers should intensify the advisory role to ensure that businesses take advantage of increase their turnovers.